2008
DOI: 10.1002/chem.200800239
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Chiral Benzylic Ether‐Bridged Periodic Mesoporous Organosilicas

Abstract: The first synthesis of a chiral periodic mesoporous organosilica (PMO) carrying benzylic ether bridging groups is reported. By hydrolysis and condensation of the new designed chiral organosilica precursor 1,4-bis(triethoxysilyl)-2-(1-methoxyethyl)benzene (BTEMEB) in the presence of the non-ionic oligomeric surfactant Brij 76 as supramolecular structure-directing agent under acidic conditions, an ordered mesoporous chiral benzylic ether-bridged hybrid material with a high specific surface area was obtained. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 30 publications
0
35
0
2
Order By: Relevance
“…[4][5][6][7][8][9] The presence of organic functional groups in mesoporous frameworks can modify the hydrophilicity/hydrophobicity of pore surface as well as the surface reactivity of PMOs, which provide the opportunity to tune mechanical, electronic, and optical properties of hybrid materials with a wide range of applications. [10][11][12][13][14][15] As a consequence, the assembly of PMOs with controlled pore architectures and morphologies has always been a global focus in this field.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9] The presence of organic functional groups in mesoporous frameworks can modify the hydrophilicity/hydrophobicity of pore surface as well as the surface reactivity of PMOs, which provide the opportunity to tune mechanical, electronic, and optical properties of hybrid materials with a wide range of applications. [10][11][12][13][14][15] As a consequence, the assembly of PMOs with controlled pore architectures and morphologies has always been a global focus in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The enantiomeric purity of the organosilicas was determined to be >95% ee in materials obtained under acidic conditions. Fro¨ba et al 183 reported the synthesis of a chiral precursor carrying benzylic ether bridging groups (54). They were able to produce pure PMOs with highly ordered mesostructures and surface area of 820 m 2 g À1 .…”
Section: Nitrogen and Sulphur Containing Bridged Pmosmentioning
confidence: 98%
“…Dies gelang durch die asymmetrische Hydroborierung an einer Ethylen-verbrückten Organosilicatvorstufe, die nach Kondensation die weitere Umsetzung zu chiralen Hydroxy-(1) [84] oder Aminogruppen (2) [85] ermöglichte. Weitere chirale PMOs wurden durch asymmetrische Hydrierung einer Ketogruppe an einer Phenyl-verbrückten Vorstufe (3), [86] durch asymmetrische Hydrosilylierung einer Phenylsilyletheneinheit (4) [87] oder durch Racematspaltung einer axial-chiralen, biphenylverbrückten Vorstufe erhalten (5). [88] Poröse Organosilicate mit stabiler Porenstruktur konnten unter alleiniger Verwendung dieser Vorstufen hergestellt werden.…”
Section: Chirale Pmosunclassified